2014
DOI: 10.1093/cid/ciu634
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Bacteria in the Pathogenesis of Escherichia coli Urinary Tract Infection in Children

Abstract: IBCs/IIB could explain a high proportion of children with recurrent UTI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 30 publications
3
80
1
1
Order By: Relevance
“…After their maturation, bacteria disperse from the IBC to invade other cells, where the IBC cycle is repeated 3840 . IBC formation is a common mechanism for clinical UPEC isolates and has been observed in multiple mouse backgrounds and also in exfoliated uroepithelial cells in the urine of patients with acute UTIs but not in the cells in urine from healthy controls 41,42 . The process of invasion and IBC formation provides UPEC with the ability to survive stringent bottlenecks in the urinary tract, including TLR4-mediated expulsion, umbrella cell exfoliation, ascension to the kidneys, urination and inflammation 7,43 .…”
Section: Adherence and Colonizationmentioning
confidence: 99%
“…After their maturation, bacteria disperse from the IBC to invade other cells, where the IBC cycle is repeated 3840 . IBC formation is a common mechanism for clinical UPEC isolates and has been observed in multiple mouse backgrounds and also in exfoliated uroepithelial cells in the urine of patients with acute UTIs but not in the cells in urine from healthy controls 41,42 . The process of invasion and IBC formation provides UPEC with the ability to survive stringent bottlenecks in the urinary tract, including TLR4-mediated expulsion, umbrella cell exfoliation, ascension to the kidneys, urination and inflammation 7,43 .…”
Section: Adherence and Colonizationmentioning
confidence: 99%
“…One study that evaluated children with E coli cystitis found intracellular bacterial in 36.8% of the patients. 38 In renal transplant recipients screened for UTIs, IBCs were visualized in 23 of 53 patients (44%), with only 1 patient deemed to have a UTI by standard bacterial culture. 39 Another study looked at women with LUTS compared with asymptomatic controls and found 75% of the LUTS patients had evidence of IBCs compared with 17% of the controls.…”
Section: Evidence For Urothelial Invasion In Humansmentioning
confidence: 98%
“…As part of the host response, the superficial facet cells are largely exfoliated [20], liberating IBCs into the urine and ridding the body of thousands of bacteria. Shed IBC-containing cells are observed in the urine of infected women and children, supporting their clinical relevance [21, 22]. After 16–24 h in murine UTI models, a subset of UPEC in remaining IBCs adopt a neutrophil-resistant, filamentous morphology and escape the IBCs, subsequently re-invading naïve bladder epithelial cells [23].…”
Section: Molecular Pathogenesis Of Utimentioning
confidence: 99%